SOME REFLECTIONS ON ANCIENT KHORAZM IRRIGATED AGRICULTURAL CULTURE - H.A. Palvanov (International Scientific and Current Research Conferences, 2025)
This in the article Ancient Khorezm watering can farming to culture circle information reflection reached to be this in the area artificial to water specialized farms and ancient water facilities and take visited archaeological research results of the area to oneself typical farming culture that there is showed scientific information based on analysis made.